2021
DOI: 10.1097/nmd.0000000000001315
|View full text |Cite
|
Sign up to set email alerts
|

Women's Knowledge of Postpartum Anxiety Disorders, Depression, and Cognitive Behavioral Therapy

Abstract: Although awareness of postpartum depression (PPD) has increased, postpartum anxiety disorders (PPA) remain overlooked. Understanding women's knowledge of PPA and their effective treatments is needed given the underutilization of treatment and associated negative health outcomes. Two internet-based studies (OSF [https://osf.io/3fjvr] preregistered follow-up) were conducted to identify women's knowledge and familiarity with PPD and PPA and knowledge of cognitive behavioral therapy (CBT). Study 1 revealed that wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The damages of PPD include difficulties with breastfeeding, behavioural functions, social interaction, and so on. 31 , 32 The pathological mechanism of PPD is multifactorial that has yet to be fully clarified. Disruption of the oxytocinergic system has received less attention until recently.…”
Section: Discussionmentioning
confidence: 99%
“…The damages of PPD include difficulties with breastfeeding, behavioural functions, social interaction, and so on. 31 , 32 The pathological mechanism of PPD is multifactorial that has yet to be fully clarified. Disruption of the oxytocinergic system has received less attention until recently.…”
Section: Discussionmentioning
confidence: 99%
“…If untreated, PPD can adversely affect the mother's health and might cause sleeping, eating, and behavioral problems for the infant (O’Connor et al, 2016). Awareness of PPD has increased, yet postpartum anxiety (PPA) disorders and other mental health difficulties (e.g., postpartum OCD, postpartum panic disorder, postpartum PTSD, and postpartum psychosis) for postpartum mothers remain underassessed and treated (Ponzini et al, 2021). Women who need additional mental health support often sought this from healthcare professionals (e.g., OBGYN), and found that when support was available, it was not always accessible and some professionals offered negative support (e.g., judgmental, offered conflicting advice, biased toward breastfeeding; Tanganhito et al, 2020).…”
Section: Mental Health In Postpartum Womenmentioning
confidence: 99%
“…Until recently, there has been a lack of discourse around prenatal anxiety in society and the literature [ 9 , 11 , 20 ], which has perpetuated several of the help-seeking barriers faced by prenatal people experiencing anxiety. Limited knowledge among the general public and healthcare providers about symptoms of perinatal anxiety and treatment options, which constitutes a key component of mental health literacy, can hinder pregnant and postpartum people’s help-seeking endeavours [ 2 , 21 24 ]. Research by Ponzini et al [ 21 ] suggests that there is a lack of clarity around symptoms of postpartum anxiety disorders, with perinatal people exhibiting greater familiarity with symptoms associated with postpartum depression.…”
Section: Introductionmentioning
confidence: 99%
“…Limited knowledge among the general public and healthcare providers about symptoms of perinatal anxiety and treatment options, which constitutes a key component of mental health literacy, can hinder pregnant and postpartum people’s help-seeking endeavours [ 2 , 21 24 ]. Research by Ponzini et al [ 21 ] suggests that there is a lack of clarity around symptoms of postpartum anxiety disorders, with perinatal people exhibiting greater familiarity with symptoms associated with postpartum depression. Further to this, qualitative research suggests that pregnant and postpartum people experiencing anxiety may not always associate their symptoms with a perinatal anxiety disorder, which can make it difficult for them to locate information and supports that address their mental health concerns [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation